Radiotherapy and Its Intersections with Surgery in the Management of Localized Gynecological Malignancies: A Comprehensive Overview for Clinicians - Fabian, Alexander (J Clin Med, 2020)
Surgery, including minimally invasive surgery, and radiotherapy are key modalities in the treatment of gynecological malignancies. The aim of this review is to offer the multidisciplinary care team a comprehensive summary of the intersections of surgery and radiotherapy in the local treatment of gynecological malignancies. Recent advances in radiotherapy are highlighted. Relevant publications were identified through a review of the published literature. Ovarian, endometrial, cervical, vaginal, and vulvar cancer were included in the search. Current guidelines are summarized. The role of radiotherapy in adjuvant as well as definitive treatment of these entities is synthesized and put into context with surgery, focusing on survival and quality of life. Although these outcomes have improved recently, further research must be focused on the number of life years lost, and the potential morbidity encountered by patients.